The effect of CEO characteristics on financial leverage: findings from listed companies in Vietnam - Nguyen Minh Ha (Taylor & Francis Group, 2021)
The research is conducted with the goal of determining the influence of CEO characteristics, including CEO experience, on the financial leverage of listed companies in Vietnam. Financial leverage is among the vital financial policies for any business. A review of upper echelons theory suggests direct influence of CEO characteristics on setting business policy and inevitably on firm financial leverage. To assess the effect of CEO characteristics on financial leverage, the paper conducts a generalized method of moments regression with the following dependent variables: CEO age, CEO experience, the level of education related to the economic industry of the CEO education, and CEO gender. The data studied consist of 770 observations on 110 companies listed on Vietnam’s two major stock exchanges, Ho Chi Minh Stock Exchange (HOSE) and Hanoi Stock Exchange (HNX), over the period 2012–2018. We found that CEO experience, CEO education, and CEO gender are significantly positively correlated with firm leverage whereas CEO age is negatively correlated. Our results also provide additional useful information for shareholders and investors in recruiting a new CEO or balancing CEO power in the business.